Perspectives in world agriculture - Commonwealth Agricultural Bureaux (Slough : Commonwealth Agricultural Bureaux, 1980)
This book has been written to commemorate the 50th anniversary of the founding of the imperial Agricultural bureau which, in 1948 was re-designated as the Commonwealth Agricultural Bureaux .
Includes bibliographical references
uaa 22/01/19
Loans.
Keywords: Agriculture; Agriculture---Resaerch